KOORDINASI PEMERINTAH DALAM MENGATASI KEMACETAN DI KOTA MEDAN SUMATERA UTARA - Ramadanil Ramadanil; Susilawati (ADMIN: Jurnal Administrasi Negara, 2023)
Background: The author focuses on the problem of high community mobility caused by the large number of motorists who use road facilities simultaneously during peak hours. If this is not supported by adequate facilities, it will cause new problems, namely congestion. Purpose: The purpose of this study is to analyze and describe Government Coordination in Overcoming Congestion in medan City, Central Java Province, identify and analyze the supporting factors and inhibiting factors ofGovernment Coordination in Overcoming Congestion in Semarang City, Central Java Province,identify and analyze efforts to overcome impediments to Government Coordination. Regions in Overcoming Congestion in the City of Semarang, Central Java Province. Methods: This study uses adescriptive qualitative method with an inductive approach and an analysis of the coordination theory proposed by Taliziduhu Ndraha. Data collection techniques using in-depth interviews (7 informants),documentation and observation. Results/Findings: the factor that hinders coordination in overcoming congestion is the shortage of personnel from the transportation agency itself. The transportation agency cannot accept personnel freely due to the available budget, competence and ability of members and other factors. Conclusion: That the coordination carried out by the medanCity Transportation Service with related agencies is good and in accordance with the coordination theory by Taliziduhu Ndraha. The supporting factors and inhibiting factors for the coordination process came from internal and external to the Department of Transportation. Efforts made to overcome the inhibiting factors are optimizing the performance of coordinating implementers with acommitment to sincere work, smart work as well as by making innovations that can be useful for the development of the Department of Transportationin the future